Probabilistic analysis of steel columns designed based on IS: 800-2007 - Joseph, J. Daniel Ronald; Rao, K. Balaji; Anoop, M. B. (Journal of Structural Engineering, 2025)
This work deals with the probabilistic analysis of steel columns designed based on IS: 800-2007. The rolled steel Isections given in Handbook for Structural engineers (SP-6(1)) are considered for the probabilistic analysis covering a practical range of slenderness ratio. Monte-Carlo simulation technique is used for the probabilistic analysis and one thousand samples are used in the simulation. Breadth of flanges, depth of web, thickness of flanges and web, Young’s modulus of steel, yield strength of the material, effective length of the column are treated as the random variables in the simulation. The CDF values of theoretical P/Py values corresponding to P/Py values estimated using IS: 800-2007 and Eurocode 3 are reported in this study.